Pharmacy's response to unwanted loneliness: social pharmacy (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Both the General Council of Pharmaceutical Associations at the national level and the Official College of Pharmacists of Valladolid at the local level have developed numerous initiatives to reduce unwanted loneliness among older adults and other particularly vulnerable groups. Pharmacies and their pharmacists are ideal places to detect situations of unwanted loneliness, provide support for these individuals, and inform the various institutions or private entities of vulnerable patients at risk of unwanted loneliness.
Keywords: pharmacy; social pharmacy; medicine; elderly person; unwanted loneliness.